Prevalence and predictors of childfree people in developing countries - Zachary P. Neal; Jennifer Watling Neal (PLoS ONE, 2025)
Childfree people—people who do not have children and do not want to have children in the future—represent and large and growing percentage of the population in wealthy countries. However, less is known about childfree people in developing countries. To facilitate this research, we developed software to identify childfree people in data from the Demographic and Health Surveys. Using this software, we estimated the prevalence of childfree people in 51 developing countries. Among single women ages 15–29, we found substantial cross-national and within-region variation in childfree prevalence, ranging from 0.3% in Liberia to 15.6% in Papua New Guinea. We also estimated the association between being childfree and country-level indicators of human development, gender equality, and political freedom. Results suggest that the prevalence of childfree people in a country is associated with the country’s level of human development, and to a lesser extent their gender equality and political freedom. These results suggest that some developing countries have large populations of childfree people, and thus that being childfree is not a choice restricted to those living in the West or in wealthy countries. As developing countries evolve in terms of their human development, gender equality, and political freedom, it will be important to continue studying their childfree populations, both to understand demographic transitions in this part of the world, and to support its members’ reproductive health and other needs.